Pengaruh Literasi Keuangan dan Life Style Terhadap Penggunaan Paylater di Kalangan Gen Z Kota Mataram - Desak Nyoman Arti; I Gede Bayu Wijaya; I Komang Widya Purnama Yasa (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Financial literacy and lifestyle are important factors influencing the use of Paylater services among Generation Z. The convenience and flexibility offered by Paylater have increased the adoption of digital financial services; however, low financial literacy and a consumptive lifestyle may lead to irresponsible usage. This study aims to analyze the influence of financial literacy and lifestyle on Paylater usage among Generation Z in Mataram City. A quantitative approach was employed with a sample of 100 respondents selected through purposive sampling. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, and F-tests. The results indicate that financial literacy and lifestyle have a significant effect on Paylater usage, both partially and simultaneously. These findings suggest that improving financial literacy and promoting a responsible lifestyle are essential to encourage wiser use of Paylater services among Generation Z.